Strengthening Educational Capacity through Context-Relevant Curriculum Design and Evaluation - Downes, Elizabeth; Wold, Judith; Belatchew, Mesrak; Mustafa, Amani; Blount, Stephen (Frontiers in Education, 2017)
There is an acute shortage of healthcare workers in Sudan. The Academy of Health Sciences was created to prepare health-care professionals in order to restore and ultimately maintain the requisite skills-mix. This necessitates transformative education using a context-relevant curricula. A context-relevant curriculum is one that is feasible, consistent with the mission of the educational institution and responsive to the communities of interest. This article describes a partnership to strengthen the local capacity of health workforce educators. The article describes one of a series of faculty development workshops, with this first aimed at the skills to develop and evaluate context-relevant curricula using community midwifery curriculum as exemplar.